The bakery of happiness - Beck, Ian (Scotland: Barrington Stoke, Edinburgh, 2019)
Perfect pains au chocolate ... hot crusty croissants ... and a voice that turns every word into a song. Paul du Pain's bakery is a very special place. Each day, Paul bakes the bread while Marie serves customers in the shop. Everyone who walks in the door walks back out feeling happier than before. But when Marie goes away, Paul's days become sad and grey. Without her, the bakery's magic is gone but will Paul ever be able to win her back?
Keywords: Children's stories